Development of Medan Labuhan Train Station - Indah Sekarini; Nelson M Siahaan (Talenta Publisher, 2018)
Development of the city center of Medan Labuhan area requires public infrastructure to support community needs activities. One of the most needs is a train station. A train station is an important part in a contemporary urban area for living, entertaining and working. Trains assessed can cope with transportation problems that occur between regions. With the above considerations, it is necessary to make efforts that can improve the condition of Medan Labuhan Train Station. The approach of a design of Medan Labuhan Station Development is the theme of Neo Vernacular Architecture so that it can be aligned with the old station and surrounding buildings and support conservation activities in Chinatown Medan Labuhan. Improvement can be done by the development of Labuhan Station is a passenger station that can accommodate all the required activities and provide services as much as possible, so that service users feel well served and support various activities center and sub-center services Medan City in the North located in Medan Labuhan The method of study there are two approaches to this approach, the observation method, and the literature method. Observation method is done with several times to survey to the location of design. While the literature method is done by collecting data, both secondary data and primary data